Molecular identification of Atlantic goliath grouper epinephelus itajara (Lichtenstein, 1822) (Perciformes: Epinephelidae) and related commercial species applying multiplex PCR - Damasceno, Jï¿½nio S. (2016)
The Atlantic goliath grouper, Epinephelus itajara, is a critically endangered species, threatened by illegal fishing and the destruction of its habitats. A number of other closely related grouper species found in the western Atlantic are also fished intensively. While some countries apply rigorous legislation, illegal harvesting followed by the falsification of fish products, which impedes the correct identification of the species, is a common practice, allowing the catch to be marketed as a different grouper species. In this case, molecular techniques represent an important tool for the monitoring and regulation of fishery practices, and are essential for the forensic identification of a number of different species. In the present study, species-specific primers were developed for the Cytochrome Oxidase subunit I gene, which were applied in a multiplex PCR for the simultaneous identification of nine different species of Epinephelidae: Epinephelus itajara, E. quinquefasciatus, E. morio, Hyporthodus flavolimbatus, H. niveatus, Mycteroperca acutirostris, M. bonaci, M. marginata, and M. microlepis. Multiplex PCR is a rapid, reliable and cost-effective procedure for the identification of commercially-valuable endangered fish species, and may represent a valuable tool for the regulation and sustainable management of fishery resources.